Gas Industri - Eva Dasmita (Balai Besar Kimia dan Kemasan, 1987)
In Indonesia the Industrial Gases Have Developed very fast, They are Oxygen, nitrogen, carbon dioxid, Acethylene and so on. Generally that gases have Followed the Indonesian Standard of Industry. According to the Directory general of chemical Basic Industry, in 1985 the Capacity of Oxygen 18,979 Million M3 /year, Nitrogen 17, 109 Million M3/year, Carbon Dioxyde 18,166 Million M3/year and Acethylene 1,729 Million M3 /year.